NATIVE AND TARGET LANGUAGE INFLUENCE ON THE STUDENTS’ INTERLANGUAGE PRODUCTION: A CASE OF INDONESIAN EFL COMPOSITIONS - Fauziati, Endang (Universitas Pendidikan Indonesia, 2017)
English compositions written by Indonesian EFL students contain erroneous sentences which portray learner language. The errors are neither of their native language nor the target language, but containing linguistic system from both. This is called an interlanguage. This study focuses on one of interlanguage features, that is, permeability, meaning the susceptibility of interlanguages to infiltration by first language and target language rules or forms. It aims to provide empirical evidence of the permeability of the students’ interlanguage production by describing the types and degree of the native and target language influence and explaining the possible causes of the influences. The data were 264 ill-formed sentences elicited from their English free compositions. Error analysis and interlanguage analysis were used as framework for collecting, identifying, describing, and explaining the data. The results indicate that their interlanguage production was influenced by their native language and the target language at both lexical and syntactical level. The dominant native language influence was on vocabulary (i.e. Indonesian borrowings) and the target language influence was on grammar (i.e. verb tenses). The native language influence had a little lower frequency compared with that of the target language. The main source of the influence was their possession of two language systems in their mind was activated regardless of their intention to use one language only. The native language influence was due to the good mastery of the native language and the limited knowledge of the target language. The target language influence was due to the learning strategy used.